PENERAPAN PENDEKATAN MATEMATIKA REALISTIK TERHADAP HASIL BELAJAR SISWA SDN 09 PONTIANAK - Lestari, Gita; Margiati, K Y; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research was "Is there any influence of realistic mathematic education to learning result of FPB and KPK of fourth grade student of State Elementary School 09 Pontianak Barat?". The research method used in this research was the experimental method with quasi experimental design (Quasi Experimental Design), with the Nonequivalent Control Group Design experiment design. The sample selection was done by simple random sampling technique. Data collection tool in the form of observation sheet, document of learning result, and test result of student learning in the form of essay matter with 10 question. Based on the statistical calculation of the average learning result of the final test of the experimental class 79,20 and the mean of final test result of control class 67,68 obtained the final test data counted 2,549 and ttable (?= 5% and dk 32 + 33 -2 = 64) of 1.670133, because tcount (2.549)>ttable (1.670133), then Ha is accepted. From the calculation of effect size (ES), obtained ES of 0.583 (medium criterion). This means the use of realistic mathematic education on learning FPB and KPK gave a moderate effect on student learning outcomes in grade IV State Elementary School 09Pontianak Barat. Keywords:Influence, Learning Outcomes, Realistic Mathematic Education.